Growth Models for Acacia nilotica Young Plantation in Semi-Arid Region of Central India - Rizvi, R. H.; Bharti, A. K.; Ahlawat, S. P. (Indian Forester, 2013)
Six years growth data of Acacia nilotica plantation was compiled and analysedstatistically. Significantly high correlations were found between height and dbh (0.93) and also between canopy diameter and dbh (0.92). Therefore, height-dbh and canopy diameter-dbh relationships have been established for A. nilotica trees. The non-linear models; Ln H=3.813+0.805D0.267 and CaD=0.438 + 0.396 D - 0.009 D2; where, H-tree height (m), D-diameter at breast height (cm) and CaD- canopy diameter (m) were developed. These models were found good fit on the basis of statistical criteria and may be used for estimating height and canopy diameter of A. nilotica trees in semi-arid region of Central India.